2022
DOI: 10.1093/reseval/rvab044
|View full text |Cite
|
Sign up to set email alerts
|

Societal targeting in researcher funding: An exploratory approach

Abstract: Shaping public research to enhance its societal contribution has become a key policy concern. Against this background, how research funding may stimulate the societal orientation of scientific research—or how funding is societally targeted—has been underexplored. This article proposes an exploratory approach to characterize societal targeting in individual researcher funding, based on four key societal targeting dimensions: interdisciplinarity, transdisciplinarity, prioritized research problems and user-orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 76 publications
(113 reference statements)
0
13
0
Order By: Relevance
“…Researchers act and strategize about (co-)use of features their funding grants afford (Hellström & Jacob, 2017). They use their specialist knowledge to leverage funding to advance their cognitive career ambitions, to contribute to growth of their knowledge communities, and to satisfy research organisations, funders and evaluators (Gläser, 2019;Thomas et al, 2020;Ramos-Vielba et al, 2022).…”
Section: Why Reframe the Study Of Research(er) Funding?mentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers act and strategize about (co-)use of features their funding grants afford (Hellström & Jacob, 2017). They use their specialist knowledge to leverage funding to advance their cognitive career ambitions, to contribute to growth of their knowledge communities, and to satisfy research organisations, funders and evaluators (Gläser, 2019;Thomas et al, 2020;Ramos-Vielba et al, 2022).…”
Section: Why Reframe the Study Of Research(er) Funding?mentioning
confidence: 99%
“…They highlight international and interdisciplinary collaboration is growing, and that more 'team science' and massively-collaborative research is now being done, as evidenced by a rising hyper-authorship of papers in selected fields. Studies have observed funders increasingly prioritising cross-sectoral, trans-disciplinary working to tackle societal challenges, thus making research more complex (Shapira & Wang, 2010;Ioannidis et al, 2018;Adams et al, 2019;Schneider et al, 2019;Wu et al, 2019;Wang & Barabási, 2021;Ramos-Vielba et al, 2022). Such work, however, does not help us determine whether most researchers now face complicated funding situations.…”
Section: Why Reframe the Study Of Research(er) Funding?mentioning
confidence: 99%
See 3 more Smart Citations